PENGARUH INOVASI PRODUK, FLEKSIBILITAS HARGA DAN LOKASI TERHADAP MINAT BELI DI BATIK ASOFA TRUSMI CIREBON - Halimatus Sya'diyah; Syaeful Bakhri; Achmad Otong Busthomi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study is motivated by the increasing competition in the batik industry in Trusmi Cirebon, which requires businesses to enhance consumer purchase intention through product innovation, price flexibility, and strategic location. The objective of this research is to analyze the effect of product innovation, price flexibility, and location on consumer purchase intention at Batik Asofa Trusmi Cirebon, both partially and simultaneously. This study employed a quantitative research method with a survey approach. The sample consisted of 100 consumers of Batik Asofa Trusmi Cirebon. Data were analyzed using multiple linear regression. The results indicate that partially, product innovation and location have a positive and significant effect on purchase intention, while price flexibility has a negative and significant effect on purchase intention. Simultaneously, product innovation, price flexibility, and location significantly influence purchase intention, with a coefficient of determination of 77.3%. In conclusion, enhancing product innovation and selecting a strategic location are key factors in increasing consumer purchase intention.